THE ROLE OF ROS IN ATHEROSCLEROSIS AND ANTIOXIDANT - Pongnimitprasert, Nushjira (Thai Bulletin of Pharmaceutical Sciences, 2023)
Living organisms require oxygen to sustain their existence, and oxidative compounds such as reactive oxygen species (ROS) and reactive nitrogen species (RNS) in cells are produced from molecular oxygen as a consequence of aerobic metabolism. ROS can be classified as either free radicals (radicals) or non-radicals (paired with electrons). Free radicals are molecules with one or more lone pairs of electrons. Therefore, they have the agility to react by receiving electrons from other substances nearby, resulting in self-stabilization. This causes other substances that lose or gain electrons to become new free radicals and will react with other substances in a chain reaction. Generating a large number of free radicals (ROS) causes cell injury, which is an important mechanism that causes various pathologies such as high blood pressure, diabetes mellitus, hypercholesterolemia, heart attack and atherosclerosis. Atherosclerosis is associated with the deterioration of lipids and hardening of the arteries. It is a disease associated with chronic inflammation, thickening and hardening of the blood vessels which is the main cause of coronary heart disease and stroke, including myocardial infarction. It is recognized that ROS plays an important role in atherosclerosis. This disrupts the equilibrium of vascular endothelial cells, which are important steps involved in fatty streak formation, atheroma induction and atherosclerotic plaques leading to thrombosis. Antioxidants are molecules that can neutralize the oxidation of ROS before they interact with cellular biomolecules, causing structural or functional changes. Antioxidants are a defense system. They are divided into two levels; 1) primary defense mechanism, a defense mechanism that directly inhibits oxidative damage by repelling free radicals before they cause molecular damage within cells. 2) secondary defense mechanism (chain-breaking defense) includes vitamin C, vitamin E and uric acid.